2022
DOI: 10.22146/ijc.70467
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Influencing Factors and Technological Processes for the Production of Orange Essential Oil (<i>Citrus sinensis</i>) on Equipment Semi-industrial Distillation

Abstract: In recent years, essential oils extracted from different plant species have become increasingly popular in the production of pharmaceuticals, cosmetics, and foods. The essential oil from orange (Citrus sinensis) is important in large-scale applications due to its antibacterial, antioxidant activities, and pleasant aroma. In this study, factors affecting the production of orange essential oil on a distillation device with an operating capacity of 50 L/batch, including the ratio of material to water, temperature… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 36 publications
1
1
0
Order By: Relevance
“…However, if the temperature is too high, there are components in the material that are degraded, thus reducing the quality of the resulting extract (Teles et al, 2017). This is in line with research conducted by Hien et al,(2022) on orange essential oil obtained at an extraction temperature of 130 °C resulting in a yield of 1.7 mL/g, but at a temperature of 150 °C the yield of essential oil decreased to 1.63 mL/g.…”
Section: Essential Oil Extractionsupporting
confidence: 82%
See 1 more Smart Citation
“…However, if the temperature is too high, there are components in the material that are degraded, thus reducing the quality of the resulting extract (Teles et al, 2017). This is in line with research conducted by Hien et al,(2022) on orange essential oil obtained at an extraction temperature of 130 °C resulting in a yield of 1.7 mL/g, but at a temperature of 150 °C the yield of essential oil decreased to 1.63 mL/g.…”
Section: Essential Oil Extractionsupporting
confidence: 82%
“…The higher the heating temperature, the faster the heat transfer and mass transfer that occur between the media and the material. Thus, the faster the material reaches its boiling point for the evaporation process (Hien et al, 2022). Several research results related to extraction time were reported by Haryanti et al, (2014), reporting the process of extracting orange fern oil in 3 h; Ikarini et al, (2021) reported that the distillation of Siamese oranges was carried out for 2 h; Febrina & Sigiro (2021) reported that the distillation of Siam Sambas oranges was carried out for 7 h; Fachriyah et al, (2002), reported distillation of Siamese orange peel essential oil for 10 h; Wibaldus et al, (2016) reported the distillation of lime for 4 h. The distillation time varies greatly also depending on the raw material, the thicker the orange peel, the longer the distillation time is needed.…”
Section: Distillation Process Temperaturementioning
confidence: 99%